HE USE OF CROSS LINKER IN UPHOLSTERY LEATHER FINISHING COATING - Putri Endah Kurnia; Laili Rachmawati; Dina Mariana Uli Lubis; Sofwan Siddiq Abdullah; Fadzkurisma Robbika (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
Leather upholstery must have good rub resistance, adhesion, and flexing resistance to be able for a long time. This study aims to determine the correct amount of cross linker use to obtain the good rub resistance, adhesion, and flexing resistance upholstery of the leather upholstery finishing coat. Crust leather, adhesive solvent, diluent solvent, penetrator, medium light polyurethane, light polyurethane, aliphatic polyurethane, cross linker, spray gun, flex meter, rubbing fastness tester, and grey scale are used as material. Upholstery leather finishing consist of base, medium and top coat. The method is addition of 2, 3, and 4% cross linker from the total of top coat composition. The result of wet rubbing resistance test are very faded (value=1) when using 2% cross linker, medium faded (value=3) when using 3% cross linker, very no faded (value=5) when using 4% cross linker. The dry rubbing resistance of each treatment showed no difference. Adhesion value (≤12.0 N) and flexing resistance (no crack) for all treatment met the requirement. It can be concluded that the use of a cross linker of 4% in the top coat finishing produces the best test value.